Working and reference check list for fireflies of Melanesia (Coleoptera: Lampyridae: Luciolinae) - Ballantyne, Lesley A.; Lloyd, James E. (Zootaxa, 2013)
Twenty-three species of Lampyridae (fifteen of them new) collected during the 1969-70 Alpha Helix scientific expedition to New Guinea are now characterized by both behavioural and taxonomic data. For ease of identification, relocation of specimens, and location of all pertinent literature this check list is presented.